(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Petrographic studies have been carried out on coal samples from Okobo coal deposit in the northern Anambra Basin of Nigeria. The studies were carried out primarily to determine the petrographic characteristics of the coal based on its composition and vitrinite reflectance. Maceral characterization reveals the presence of the three maceral groups; vitrinite, liptinite and inertinite in all the samples. Generally, the proportion of the vitrinites and inertinites are higher than the liptinites in the samples. On mineral matter-free basis, the coal, on average, contains 65.10 % vitrinite, 11.30 % liptinite and 23.60 % inertinite. With mineral matter counted, on average, it consists of 57.10 % vitrinite, 10.20 % liptinite, 21.50 % inertinite and 11.20 % mineral matter. The coal, on average, also contains 67.30 % reactives (vitrinite + liptinite) and 32.70 % inerts (inertinite + mineral matter). It has mean vitrinite reflectance measurement of 0.54 % Romax on average. These petrographic characteristics suggest that the coal does not possess coking qualities suitable for coke making blends for metallurgical processes such as iron and steel manufacture thereby placing it on low quality and non-coking. However, it is good for electricity generation. The coal is appropriate in heating boilers and ovens in industrial heating process. The cement, glass, ceramics, paper and brick industries can use it for this purpose.